Pengaruh Laju Alir Terhadap Substrat Pada Fermentasi Reject Nanas Menjadi Bioetanol Secara Kontinu - Okky Rizky Sinaga; Adrianto Ahmad; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Today, the world's need for energy is increasing while the supply of energy from fossil fuels that have been relied upon a limited number. Therefore, it is necessary that alternative energy sources are able to overcome the energy crisis. One of the alternative energy sources are being developed is bioethanol. Bioethanol can be produced by fermentation of glucose using the yeast Saccharomyces cerevisiae. One of source of glucose is pineapple. This research aims to make bioethanol from pineapple fruit skin using continuous fermentation method with a flow rate variations. Fixed variable used is the 5-liter, pH 4.5, inoculum levels of 0.3%, 0.5% urea, phosphorus levels and temperature fermentation 0.08% used is room temperature. Variable changes used are changes in feed flow rate is 5 L / day; 2.5 L / day; 1.67 L / day; 1:25 L / day and 1L / day. Experimental procedure includes pretreatment, inoculation, fermentation and purification using a vacuum evaporator. Analysis performed is analyzing glucose and ethanol concentration analysis. The results were obtained concentration of ethanol in the steady state condition for the flow rate of 5L / day as much as 5% v / v; 2.5 L / day by 7% v / v; 1.67 L / day as much as 6.5% v / v; 1.25 L / day as much as 6% v / v; and 1 L / day as much as 4% v / v. The highest ethanol concentration was obtained at a flow rate of 2.5L / day as much as 7%. This study suggests that the concentration of ethanol fermentation results increases with the flow rate of the substrate to achieve the optimal flow rate then decreased after reaching the optimum flow rate.Keywords: bioethanol, continuous, pineapple skin, saccharomyces cerevisiae